Healthcare professionals' perception and satisfaction with mental health tele-medicine during the COVID-19 outbreak: A real-world experience in telepsychiatry - Roncero, Carlos; Remon-Gallo, Diego; Casado-Espada, Nerea; Aguilar, Lourdes; Gamonal-Limcaoco, Sinta; Gallego, María Teresa; Bote, Berta; Montejo, Angel Luis; Buch-Vicent, Barbara (Frontiers in Psychiatry, 2022)
Background The use of telemedicine is increasingly being implemented, showing numerous benefits over other methods. A good example of this is the use of telemedicine following the breakdown caused by the COVID-19 pandemic. Previous experiences with telemedicine (TM) have not been significantly explored in relation to the professionals' own perspectives. Objective Identify and explore the perceptions and interests of mental health professionals who have performed TM during the period of pandemia. Methods A questionnaire on mental health professionals' perceptions of and satisfaction of TM, the Font Roja Work Satisfaction Questionnaire, was adapted and used. Data collected included 112 Psychiatric Service professionals who conducted TM in March 2020, after the country had been under lockdown for 10 weeks. Over 12.000 medical consultations were carried out by the phone, showing an overwhelming response to this method. Results High levels of satisfaction were recorded amongst professionals. TM would function as a complement to the traditional system of face-to-face visits (n-112, f-109, 96.5%). Only 9.7% (f-11) believed that digital or virtual interventions would completely replace face-to-face visits. 60.8% did not consider this monotonous work. The older the health workers were, the more satisfied they felt during their follow-up telephone consultation. The greater the previous experience, the more satisfaction was shown. There were gender differences: female mental health workers reported a greater level of comfort. Conclusion TM can be implemented with less effort, but it requires time, methods, and resources to be managed. Satisfaction among professionals is high, especially among those with more clinical experience. Patient satisfaction must be contrasted against this.